Dampak Pembelajaran Berdiferensiasi terhadap Peningkatan Literasi Siswa Bahasa Indonesia Kelas 1 SDN Latsari - Imam Ali Ma’sum Ghozali; Puji Rahayu; Novita Dewi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the effect of implementing differentiated learning on improving students' literacy skills in the Indonesian language subject, Chapter 3. Differentiated learning is an approach that considers differences in methods, materials, and assessments based on each student's initial understanding and characteristics. The learning process begins with explaining the objectives, observing students' initial understanding through pre-assessment or questionnaires, exploring learning needs, facilitating learning activities according to students' needs, and ends with reflection and planning for further learning. This research was conducted in Grade 1 of SDN Latsari Tuban with a total of 28 students. The method used was classroom action research (CAR), carried out in two cycles. The results showed an improvement in students' literacy skills, both in terms of the average score and the percentage of mastery learning achievement, although the increase was not very significant. These findings highlight the importance of adapting the learning process to students' initial understanding and individual characteristics to support more effective literacy development.